Perceived stress among gravid and its effect on their oral health in Sri Ganganagar, Rajasthan, India - Goyal, Nikita; Singh, Simarpreet; Mathur, Anmol; Gupta, Neha; Makkar, Diljot K.; Aggarwal, Vikram P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The gestation period presents unique stresses that challenges overall psychological adaptation of a women. The present study is designed especially to focus on evaluating the effect of perceived stress on pregnant women and its effect on their oral health. Methods: A cross-sectional study was conducted among 18-30 years old, pregnant women in the Sri Ganganagar city. Prior to the clinical examination a questionnaire was used in order to collect the information which comprised of three parts and were completed through an interview. The first part comprised of demographics questionnaire, second part included oral hygiene questionnaire and third part was perceived Stress Scale. Descriptive analysis described demographics and socioeconomic characteristics. Multivariate analysis was used to describe the association between stress and various characteristics. Chi-square and Kruskal-wallis test was used to study the association of independent variables with level of stress. Results: The high stress was reported among those females who were aged > 25 years (46.66%), living in rural areas (73.33%), were employed (57.77%), were in third trimester of pregnancy (96.66%) and had no previous pregnancy experience (67.77%). The mothers in high stress group had high levels of dental diseases when compared to the other two groups (low and moderate stress). Conclusions: Based on the results, this study emphasizes on the need for a continued effort to improve the mental and oral health status of gravid women so as to reduce the incidences of psychological and physical troubles in this population predicted.